Interpretation of Qiwamah According to Quraish Shihab and Husein Muhammad in QS. Al-Nisa [4]: 34 - Jabbar, Ibrahim Abdul; Shamsu, Lilly Suzana binti Haji (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2025)
This research explores the concept of qiwamah (men's leadership over women) as outlined in Qur'an 4:34, focusing on the interpretations of Quraish Shihab and Husein Muhammad. It examines how these interpretations address both traditional understandings and their applicability to modern social contexts. Employing a qualitative and comparative approach, the study draws on primary sources, such as Tafsir Al-Misbah and Husein Muhammad's writings, alongside additional literature. The findings highlight that the Qur'an attributes men's leadership to their inherent advantages and financial responsibilities. Quraish Shihab interprets this verse as universally valid, while Husein Muhammad views it as context-dependent and adaptable to contemporary conditions. Both scholars engage with the division of leadership roles in domestic and public spheres, yet their approaches reflect differing perspectives on its relevance to current societal norms.